Ginsenoside Rc attenuates DSS-induced ulcerative colitis, intestinal inflammatory, and barrier function by activating the farnesoid X receptor - Tang, Kaijia; Kong, Danli; Peng, Yuan; Guo, Jingyi; Zhong, Yadi; Yu, Haibing; Mai, Zhenhua; Chen, Yanling; Chen, Yingjian; Cui, Tianqi; Duan, Siwei; Li, Tianyao; et al. (Frontiers in Pharmacology, 2022)
Objectives: Farnesoid X receptor (FXR) activation is involved in ameliorating inflammatory bowel disease (IBD), such as ulcerative colitis (UC), and inflammatory regulation may be involved in its mechanism. Ginsenoside Rc (Rc), a major component of Panax ginseng, plays an excellent role in anti-inflammatory processes. Our aim was to explore the alleviative effect of Rc on dextran sulfate sodium (DSS)-induced inflammation and deficiencies in barrier function based on FXR signaling. Materials and Methods: In vitro, we treated human intestinal epithelial cell lines (LS174T) with LPS to explore the anti-inflammatory effect of Rc supplementation. In vivo, DSS-induced IBD mice model were established, and the changes in inflammatory and barrier function in colons after Rc treatment were measured using the disease activity index (DAI), hematoxylin and eosin (H&E) staining, immunofluorescence, ELISA, and qPCR. Then, molecular docking analysis and qPCR were used to analyze the binding targets of Rc. DSS-induced FXR knockout (FXR-/-) mice were used for further validation. Results: Rc significantly recovered the abnormal levels of inflammation indexes (TNF-α, IL-6, IL-1β and NF-KB) induced by LPS in LS174T. DSS-induced C57BL/6 mice exhibited a significantly decreased body weight and elevated DAI, as well as a decrease in colon weight and length. Increased inflammatory markers (TNF-α, IL-6, IL-1β, ICAM1, NF-KB, F4/80, and CD11b displayed an increased expression) and damaged barrier function (Claudin-1, occludin, and ZO-1 displayed a decreased expression) were observed in DSS-induced C57BL/6 mice. Nevertheless, supplementation with Rc mitigated the increased inflammatory and damaged barrier function associated with DSS. Further evaluation revealed an activation of FXR signaling in Rc-treated LS174T, with FXR, BSEP, and SHP found to be upregulated. Furthermore, molecular docking indicated a clear interaction between Rc and FXR. However, these reversal abilities of Rc were not observed in DSS-induced FXR-/- mice. Conclusion: Our findings suggest that Rc may ameliorate inflammation and barrier function in the intestine, in turn leading to the attenuation of DSS-induced UC, in which Rc may potentially activate FXR signaling to protect intestines from DSS-induced injury.